Measurements of composite Skyrmions at filling factor 1/3 - Leadley, DR; Nicholas, R; Maude, D; Utjuzh, A; Portal, J; Harris, J; Foxon, C (1998)
Measurements of the fractional quantum Hall effect energy gaps at high pressures are presented that provide evidence for the existence of composite Skyrmions. Just as charged spin textures known as Skyrmions are thought to be the lowest lying excitations for electrons at v = 1, we show that composite Skyrmions can be formed at v = 1/3 when the electron g-factor is sufficiently small. (C) 1998 Elsevier Science B.V. All rights reserved.